A simulation based approach to realize green factory from unit green manufacturing processes. (1st May 2018) - Singh, Amandeep; Philip, Deepu; Ramkumar, J.; Das, Mainak
Abstract: Manufacturing is a transformation process where various inputs get transformed to products or sub-assemblies that satisfy unmet needs. Raw materials, energy, cutting fluids, processes, etc. are inputs whereas waste, emissions, finished items, etc. form outputs. Industrial sector utilizes about 37% of the global energy production and hence, manufacturing must employ more efficient approaches and technologies to realize the sustainable society dream. Sustainable manufacturing aims at the same output with lesser input thereby reducing overall consumption, environmental impacts, and waste. Theories and approaches proposed to realize sustainable manufacturing are usually complex, devoid of practical guidelines, and focuses mostly on the energy component. Aspects of manufacturing like pollution control, waste reduction, worker environment factors like noise and aerosol, etc. and their impact on sustainability are not significantly researched yet. Guidelines for systematic analysis of manufacturing facilities, specifically the unit manufacturing processes are necessary to identify improvement opportunities. This work developed a practical approach to mathematically describe relationships between various process variables to energy consumption, waste reduction, and worker environment. Four unit manufacturing processes, viz., grinding, drilling, milling, and micro-EDM were modeled and their corresponding process parameters were optimized using Artificial Bee Colony algorithm (ABC) to improve the 'greenness' of these processes. A hypothetical flow shop facility comprising of these four optimized green unit manufacturing processes was modeled using Technomatix Simulation software. This flowshop was numerically simulated to realize a target throughput while minimizing environmental impacts, energy, and waste. The milling, drilling, grinding, and μ-WEDG process operating at green parameter settings demonstrated 29%, 16%, 31%, and 42% savings in energy respectively; resulting in a total saving of 28% in the variable energy of the overall factory. Also, the results demonstrated around 92% reduction in the usage of cutting fluids. Further, complete substitution of the non-biodegradable cutting fluids without compromising process parameters was also demonstrated.